2014
DOI: 10.1016/j.yhbeh.2014.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Frank Beach Award Winner: Steroids as neuromodulators of brain circuits and behavior

Abstract: Neurons communicate primarily via action potentials that transmit information on the timescale of milliseconds. Neurons also integrate information via alterations in gene transcription and protein translation that are sustained for hours to days after initiation. Positioned between these two signaling timescales are the minute-by-minute actions of neuromodulators. Over the course of minutes, the classical neuromodulators (such as serotonin, dopamine, octopamine, and norepinephrine) can alter and/or stabilize n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 162 publications
(197 reference statements)
2
27
0
Order By: Relevance
“…Connectomics has already begun to map out large-scale neural circuit diagrams, including ultrastructural analysis of the human brain [109,110]. It is noteworthy that neural circuits do not have fixed connective properties and the relative concentrations and mixture of neuromodulators at any given moment can provide yet another layer of dynamic functional connections within a circuit [109].…”
Section: Neurocircuitry and Perimenopausal Psychopathologymentioning
confidence: 99%
See 2 more Smart Citations
“…Connectomics has already begun to map out large-scale neural circuit diagrams, including ultrastructural analysis of the human brain [109,110]. It is noteworthy that neural circuits do not have fixed connective properties and the relative concentrations and mixture of neuromodulators at any given moment can provide yet another layer of dynamic functional connections within a circuit [109].…”
Section: Neurocircuitry and Perimenopausal Psychopathologymentioning
confidence: 99%
“…on the timescale of hours or days) [109]. The production of steroid hormones within brain circuits can rapidly modulate their functional connectivity, thereby affecting the behavior [109]. Effects of long-term 17-β estradiol (E2)…”
Section: Neurocircuitry and Perimenopausal Psychopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research demonstrated that steroids can function in a "neurotransmitter-like" way, being synthesized at precise spatial locations within neural circuits in the brain and acting within minutes as local neuromodulators that rapidly regulate cognitive functions and behavior [24][25][26][27].…”
Section: Non-genomic Actionmentioning
confidence: 99%
“…For example, estradiol shapes auditory tuning in midshipmen fish so that, during the breeding season, females are more sensitive to the harmonics in the calls of courting males, which enhances the adaptive coupling of the sender and the receiver for reproductive success (Sisneros, 2009a,b,c;Sisneros et al, 2004). Similar mechanisms of estradiol-dependent modulation of acoustic communication circuits are present in birds in response to plasma estradiol (Maney et al, 2006(Maney et al, , 2008Maney and Pinaud, 2011;Sanford et al, 2010) and locally produced neuroestrogens (Krentzel and Remage-Healey, 2015;Pawlisch and Remage-Healey, 2015;Remage-Healey, 2012, 2014RemageHealey et al, 2010RemageHealey et al, , 2008Remage-Healey and Joshi, 2012).…”
Section: Introductionmentioning
confidence: 99%